THE EFFECT OF SERVICE QUALITY AND CUSTOMER SATISFACTION ON PT. ARCHIPELAGO TOURISM TOUR - Risda Novita Sari,; Wahid Akbar Basudani,; Adam Hidayah,; Purwadi, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Tourism is a trip planned by someone for a certain time from one place to another, the purpose of which is for entertainment or hobbies so that their wishes are fulfilled. The development of tourism in Indonesia is currently increasing rapidly, however, as is well known, for the last two years people have experienced isolation, restrictions on social activities, bans on traveling and closure of the country from foreign tourists due to the pandemic, which has triggered people to take revenge travel which involves emotional and tend to exaggerate. According to a report from the Central Statistics Agency (BPS), Indonesia's domestic tourism sector consistently shows recovery in 2022 after being hit by a pandemic in 2022. The purpose of this study was to determine whether there is an effect of service quality and customer satisfaction on customer loyalty at PT. Ziara Wisata Nusantara, this study used a quantitative method of analysis with SPSS 26. The number of samples in this study amounted to 170 with the slovin sampling technique. The results of this study obtained that the variable Service Quality (X) has an influence value of 0.60 and the Customer Satisfaction variable (Y) has an influence value of 0.60. Then the simultaneous Service Quality is 0.595 with a significance value of 0.000 <0.05. Thus it can be said that the research hypothesis is accepted because the Service Quality Variable has a moderate positive influence on Customer Satisfaction Variables.